DARI TANAH MENJADI BERKAH: IMPLEMENTASI PRINSIP EKONOMI SYARIAH PADA INDUSTRI BATU BATA DI DESA MOJOSULUR, MOJOKERTO - Yani; Ilvi Nur Diana (LPPM Institut Agama Islam Uluwiyah Mojokerto, 2024)
This study examines the implementation of Islamic economic principles in the brick industry of Mojosulur Village, Mojokerto. Using a qualitative method involving interviews, observation, and documentation, the research reveals that Sharia values are reflected in halal and beneficial production, fair employee welfare, and honest, responsible distribution. The implementation illustrates that Islamic economic principles can be effectively applied in small-scale industries to promote community prosperity and economic blessings.